Secularização e resistência no Vale do Cotinguiba : o caso dos penitentes de Laranjeiras-SE - Tavares, Jorge Alberto Vieira (2023)
This dissertation addresses secularization and resistance in the Cotinguiba Valley, with a focus on the penitents of Laranjeiras, Sergipe. The research aims to understand the practice of penance as a secular tradition, where the faithful seek forms of gratitude for their sins. Additionally, it investigates how the penitents of Laranjeiras perceive the process of secularization and how the brotherhood has been resisting, considering challenges such as member deaths, lack of discipline, and attire. Some groups resort to sensationalism to gain visibility and existence. The work also seeks to comprehend the relationship between the body and sin as a requirement for belonging to the group, as well as the characteristics preserved by the penitents in the face of secularization in the Cotinguiba Valley. The employed methodology is ethnographic, utilizing observation, interviews, and photographic records as data collection techniques. It is expected that this work will contribute by exploring previously undiscussed issues and offering opportunities for future reflections by other researchers. Furthermore, it highlights the relevance of the Penitents of Laranjeiras as a significant expression both for the city and for human expressiveness.